If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -5n = -4 + 3n + 8 Reorder the terms: 12 + -5n = -4 + 8 + 3n Combine like terms: -4 + 8 = 4 12 + -5n = 4 + 3n Solving 12 + -5n = 4 + 3n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-3n' to each side of the equation. 12 + -5n + -3n = 4 + 3n + -3n Combine like terms: -5n + -3n = -8n 12 + -8n = 4 + 3n + -3n Combine like terms: 3n + -3n = 0 12 + -8n = 4 + 0 12 + -8n = 4 Add '-12' to each side of the equation. 12 + -12 + -8n = 4 + -12 Combine like terms: 12 + -12 = 0 0 + -8n = 4 + -12 -8n = 4 + -12 Combine like terms: 4 + -12 = -8 -8n = -8 Divide each side by '-8'. n = 1 Simplifying n = 1
| 2(x+4)+3=2x+2 | | 4t-3t+9=93 | | 1.5x-2.4=9.6 | | 3(4y+8)=2(6y+12) | | 8(2x-3)=16x | | 6(x-6)-4(x-5)+7x= | | 28x=11x+102 | | .30+140=s | | 2(x-3)=5x+24 | | 5(x+1)=4(x-1) | | M+(-4)=7 | | 7x+2y=88 | | 4x-9-x=3(x-12) | | x^3+cx+1=0 | | 4+10(7+w)= | | 750+22(x-12)=650+30n-300 | | 3x-2y+4z=8 | | 5.4+0.2x=1.4+8.6 | | y=9-(1)(1) | | (3x+7)(x-4)=0 | | 5+2v=9 | | 6=3y-3 | | y=9-(-1)(-1) | | 3-(2-n)+1=2(2-n) | | 54-11+6q=97 | | 5(8+2)=-3(8-38) | | 3h+1=7 | | A=x+5+z | | 4(7-a)-3= | | 5(8+2)=-3 | | 6n+4=4n+3 | | 9+8(x-4)=4-8(x-4) |